EXPLORING TEACHERS’ PRACTICE OF CLASSROOM-BASED ASSESSMENT - Hai An, Trinh (HNUE Journal of Science: Journal of Educational Science, 2025)
This study explores teachers’ practice of classroom-based assessment (CBA) and how the institutional guidelines affect their practice, using the grounded theory approach. Data were collected from interviews with four EFL teachers from a Vietnamese university and the syllabus documents they used for their classes. Results demonstrate that the participants actively planned assessment opportunities, provided necessary information of assessment to their students, and carried out the planned or unplanned assessments. All teachers reported using the assessment information to improve their teaching activities. Lastly, syllabus documents had a strong impact on the teacher’s CBA practice. Based on these findings, a conceptual model is proposed to represent the relationship between teachers’ practice and contexts and teacher assessment identity.